Chiral cyclopalladated complex promoted asymmetric synthesis of diester-substituted P,N-ligands via stepwise hydrophosphination and hydroamination reactions - Chen, Ke (2013)
A series of enantiomerically pure 1,2-diester substituted P,N-ligands incorporating two chiral carbons in the backbone were generated in high yields and high stereoselectivity from acetylenedicarboxylate via initial hydrophosphination using diphenylphosphine followed by hydroamination with various primary and secondary amines. The reactions were activated and stereochemically controlled by the organopalladium complex containing ortho-palladated (S)-(1-(dimethylamino)ethyl)naphthalene under mild conditions. The absolute stereochemistry and the coordination chemistry of P,N-products were determined by the single crystal X-ray diffraction analysis. All the chiral P,N-ligands could be liberated from the palladium template without loss of optical purity. Subsequent recomplexation to selected chiral palladium centers confirmed the optical purity of the new functionalized chiral P,N-ligands.